MUTU PENDIDIKAN: KERJASAMA GURU DAN ORANG TUA - Nanat Fatah Natsir; Ade Aisyah; Hasbiyallah Hasbiyallah; Mahlil Nurul Ihsan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The main problem of the low quality of education is that the person most responsible for education (parents) has given full trust to the teacher in the school so that the purpose of this study is how partnership between parents and teachers is intertwined in improving the quality of education in the school. Based on the theory that parents have a big role to play in the quality of school education and their participation can improve performance, especially in the foundation stage of the education system. This research method is to use qualitative research with sampling methods for parents and teachers in their expectations and forms of participation in improving the quality of education. The results of this study indicate that the expectation of parents and teachers is hight to build partnership and the form of their involvement is to constantly improve communication between them and ready to give fully what teachers need for their children's education.